2006
DOI: 10.1038/nature04721
|View full text |Cite
|
Sign up to set email alerts
|

Hexon-chimaeric adenovirus serotype 5 vectors circumvent pre-existing anti-vector immunity

Abstract: A common viral immune evasion strategy involves mutating viral surface proteins in order to evade host neutralizing antibodies. Such immune evasion tactics have not previously been intentionally applied to the development of novel viral gene delivery vectors that overcome the critical problem of anti-vector immunity. Recombinant, replication-incompetent adenovirus serotype 5 (rAd5) vector-based vaccines for human immunodeficiency virus type 1 and other pathogens have proved highly immunogenic in preclinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
381
4
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(410 citation statements)
references
References 22 publications
18
381
4
3
Order By: Relevance
“…25 In most cases, alternative serotype Ads are not cross-neutralized by antibodies directed against another serotype. 26,27 Furthermore, the incidence rate of seroconversion to many alternative serotype HAds in many cases are significantly lower than the seroconversion rates noted for HAd5. 28 These facts have justified multiple investigations into the use of alternative serotype Ads for potential use in numerous human gene transfer applications.…”
Section: Alternative Serotype Ads Exhibit Significantly Different Biomentioning
confidence: 99%
“…25 In most cases, alternative serotype Ads are not cross-neutralized by antibodies directed against another serotype. 26,27 Furthermore, the incidence rate of seroconversion to many alternative serotype HAds in many cases are significantly lower than the seroconversion rates noted for HAd5. 28 These facts have justified multiple investigations into the use of alternative serotype Ads for potential use in numerous human gene transfer applications.…”
Section: Alternative Serotype Ads Exhibit Significantly Different Biomentioning
confidence: 99%
“…34,35 A hexon-switch experiment would help understand whether anti-fiber NAbs are unique with regard to sero-switching for efficacy, or whether the same might be true for any anti-capsid NAb. 36 Moreover, completely non-Ad5 serotypes might be useful, 13,28,37,38 if the appealing attributes of Ad5 (for example, high gene expression, in vivo stability, easy production, safety) can be retained. This should not be taken for granted, as Ad5 has become the single most popular gene therapy vector because of these attributes, and there is no guarantee that they would apply to other serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…There are recent reports in mice and rhesus macaques that pre-existing immunity to Ad5 did diminish the response to Ad5-vectored vaccines [90,91], however, another study in mice using Ad5-vectors have found that pre-existing immunity did not prevent the development of immunity [92]. Priming with DNA plasmids expressing the gene of interest may be sufficient to overcome pre-existing immunity to the viral vector; however, to date this has only been demonstrated in mice [93][94][95]. Other serotypes that are not as prevalent in the human population (or that do not typically infect humans at all) might be used in place of Ad5 [90] but the original studies would have to be repeated with the new constructs to demonstrate comparable protection.…”
Section: Adenovirus-based Vaccinesmentioning
confidence: 99%